The Feminine Nature: Goddess Figures and Their Ecological Meanings in the Classical Period of Nusantara - Krisnanda Primaditya; Soma Surya Persada; Aris Agus Styawan (UIN Raden Mas Said Surakarta, 2026)
This study explores the relationship between feminine spirituality and the environment within the Hindu-Buddhist traditions of the Nusantara. Feminine spirituality in this context refers to the representation of goddesses as symbols of a fertile, harmonious and sacred nature. The concept of “feminine nature” reflects the understanding of nature as a living entity associated with the female body and energy—a worldview articulated visually through reliefs, statues, and mythological narratives during the classical period of the Indonesian archipelago. Through iconographic analysis of figures such as Dewi Sri, Parwati, Tara and Durga in their local contexts, this research demonstrates that these goddesses functioned as objects of worship and as mediums for conveying ecological values rooted in the cosmology of agrarian and maritime societies. The interdisciplinary approach—combining cultural history, visual archaeology, and ecofeminist theory—offers a new interpretation of spiritual heritage as a normative system containing moral and ecological ethics. By situating goddess figures within their historical context, this paper aims to reconstruct the ecological imagination of the Hindu-Buddhist era as a cultural legacy that remains relevant in contemporary discourses on environmental justice and feminism. This study also paves the way for the reinterpretation of local heritage that has long remained marginalized in global feminist discourse.